1992
DOI: 10.1007/bf01607048
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of E-cadherin adhesion molecule expression in human gastric cancer

Abstract: E-cadherin (ECD) is one of subclasses of the cadherin family which plays a major role in the maintenance of intercellular adhesion in epithelial tissues. An immunohistochemical study of ECD expression was performed on gastric adenocarcinoma from 103 patients using our monoclonal antibody for human ECD (HECD-1). ECD was strongly expressed in normal gastric epithelium without exception; however, various staining patterns were observed in cancer tissues. The frequency of tumours with preserved ECD expression (Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
67
1
7

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 28 publications
15
67
1
7
Order By: Relevance
“…A germline mutation in E-cadherin associated with familial gastric cancer was recently reported in a New Zealand kindred (Guilford et al, 1998). Mutations in α-and β-catenins have not been convincingly demonstrated, but protein expression abnormalities are relatively frequent, and occur in both diffuse and intestinal cancers (Oka et al, 1992;Matsui et al, 1994;Jawhari et al, 1997). We have confirmed a high frequency of expression abnormalities for all three molecules studied.…”
Section: Discussionsupporting
confidence: 63%
“…A germline mutation in E-cadherin associated with familial gastric cancer was recently reported in a New Zealand kindred (Guilford et al, 1998). Mutations in α-and β-catenins have not been convincingly demonstrated, but protein expression abnormalities are relatively frequent, and occur in both diffuse and intestinal cancers (Oka et al, 1992;Matsui et al, 1994;Jawhari et al, 1997). We have confirmed a high frequency of expression abnormalities for all three molecules studied.…”
Section: Discussionsupporting
confidence: 63%
“…28 Recent studies have demonstrated that loss of E-cadherin immunoreactivity may correlate with a lack of differentiation and aggressive behavior of breast, head and neck, lung, gastric, esophageal, colorectal, prostatic and urothelial carcinomas. [5][6][7]15,[29][30][31][32][33][34][35] Published studies on urothelial carcinoma show that loss of membranous E-cadherin immunoreactivity is strongly correlated with high grade and advanced stage. 8,12,15,[36][37][38] Whether or not loss of E-cadherin is correlated with disease progression or has any prognostic significance has been debated by several investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the CDH1 gene and loss of normal E-cad expression were involved more frequently in diffuse type than in intestinal type tumors (88% vs 48%; P = 0.006). However, the percentage of reduction in E-cad expression of GC varies from 17% to 92% in previous reports [8][9][10][11][12][13] Promoter polymorphism Li et al [22] reported that the A allele of the -160C/A promoter polymorphism alters transcriptional binding, resulting in a reduction in transcriptional efficiency of 68% relative to that of the C allele. In our study, there was no significant difference in the frequency of the C/A + A/A genotypes between diffuse and intestinal type tumors.…”
Section: Discussionmentioning
confidence: 99%
“…E-cad gene (CDH1) is an important putative tumor suppressor gene. In gastric carcinomas (GCs), the reduction in E-cad expression activation of Ecad gene varies from 17% to 92%, and is more frequent in diffuse type than in intestinal type tumors [8][9][10][11][12][13] . Germline mutation of the CDH1 gene is found in all familial GCs [14,15] .…”
Section: Introductionmentioning
confidence: 99%